Advanced global indicator of short and long term for the economy of Cauca 1960-2014 - Gómez Sánchez, Andrés Mauricio; Sarmiento Castillo, Juliana Isabel; Fajardo Hoyos, Claudia Liceth (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper proposes to build a leading or advanced indicator to the economy of Cauca department, through three alternative methodologies that depart from the traditional methodology based on National Bureau of Economic Research (NBER). Three indicators are proposed to achieve this, both short and long term, under the method of linear decomposition of the cycle, another synthetic overall indicator based on the methodology of the main components and finally another using the Kalman filter algorithm. The results show, among other things, that the indicator on Kalman scenario exceeds in statistic robustness the other two indicators and predicts a positive economic growth for the region in the coming years.